Sangeetha Pulapaka
0

STEP 1: Recall what is a quadratic equation

 https://www.qalaxia.com/viewDiscussion?messageId=5ce3853387bc8a0583b3ebaf         

STEP 2: Recall what is a quadratic formula

https://www.khanacademy.org/math/algebra/quadratics/solving-quadratics-using-the-quadratic-formula/v/quadratic-formula-3





                     STEP 3:   Identify a, b, and c and plug them into the quadratic formula. In this case a = 1, b = –8, and c = 14


\frac{-b\pm\sqrt{b^2-4ac}}{2a}


Use the order of operations to simplify the quadratic formula.

p = \frac{8\pm\sqrt{8^2-56}}{2}


              Simplify the radical, if you can. In this case you can simply the radical into:

p = \frac{8\pm\sqrt{8}}{2}

                        Reduce the problem, if you can. In this case you can reduce the entire    

                      problem by 2, to get p = 4\pm\sqrt{2}

  

                      This is how you solve for p using the quadratic formula.